1987
DOI: 10.1063/1.337957
|View full text |Cite
|
Sign up to set email alerts
|

Heteroepitaxial growth of SrO films on Si substrates

Abstract: Articles you may be interested inFabrication of Sr silicate buffer layer on Si(100) substrate by pulsed laser deposition using a SrO target

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…A number of reported attempts to grow oxide structures on silicon have been made [12][13][14][15], but until now there has been no definitive proof that a commensurate crystalline oxide-on-silicon interface could be obtained. While recent years have seen extensive studies of the synthesis of FIG.…”
mentioning
confidence: 99%
“…A number of reported attempts to grow oxide structures on silicon have been made [12][13][14][15], but until now there has been no definitive proof that a commensurate crystalline oxide-on-silicon interface could be obtained. While recent years have seen extensive studies of the synthesis of FIG.…”
mentioning
confidence: 99%
“…To achieve additional controllability of the thin film transistor (TFT) based on this concept, there have been numerous attempts to include a third carrier suppressor since the use of Ga was reported by Hosono et al [1][2][3][7][8][9][10][11][12]. SrO is a known electrical insulator [13][14][15][16] with a bandgap of 5.7 eV [13], an electronegativity of 0.95, and a dielectric constant of 3.2 [17]. Because Sr satisfies the basic condition of being a carrier suppressor, having a large bandgap and a low electronegativity [1,9], we recommend it as the third component of a solution-processed IZO system.…”
Section: Introductionmentioning
confidence: 99%
“…1,14 On the other hand, the Ru-Si-O system, as has been mentioned already, has a stable tie-line not between RuO 2 and Si but between Ru and SiO 2 at ¾1000 K. This suggests that RuO 2 C Si ) Ru C SiO 2 G°1 000 K ¾ D 595 kJ mol 1 is favourable for all possible reactions in the RuO 2 /Si contact system. 1 Furthermore, this value is more negative than the energy of formation of SrRuO 3 G°1 000 K ¾ D 325 kJ mol 1 at 1000 K. 13 The reduction into elemental Ru by Si at the initial stage of growth is believed to be the most favourable candidate reaction leading to the unstable contact of SrRuO 3 on Si. Based on the structural and chemical information from reaction layers and with the help of thermodynamic calculations we propose the possible reaction thermodynamics for the SrRuO 3 /Si contact system as follows.…”
mentioning
confidence: 98%
“…Although the thermodynamic calculations for SrO in contact with Si could not be completed due to the absence of thermodynamic data for SrSi 2 and Sr 3 SiO 5 , it has been reported that SrO and Si are thermodynamically stable when in contact at temperatures of >1000 K. 1 Furthermore, SrO can be grown epitaxially on an Si substrate of cube-on-cube type. 13 In general, it is known that alkaline earth oxides such as BeO, MgO, CaO, SrO and BaO, in which divalent cations can act as a network modifier in SiO 2 amorphous glass, are stable when in contact with Si. 1,14 On the other hand, the Ru-Si-O system, as has been mentioned already, has a stable tie-line not between RuO 2 and Si but between Ru and SiO 2 at ¾1000 K. This suggests that RuO 2 C Si ) Ru C SiO 2 G°1 000 K ¾ D 595 kJ mol 1 is favourable for all possible reactions in the RuO 2 /Si contact system.…”
mentioning
confidence: 99%